Considering uncertainties in power system transient stability analysis - Fortulan, Raphael Luiz Vicente (2019)
Alternative renewable energy sources such as solar, wind, and bio energy have brought uncertainties into the power flow of electric power systems. Purely deterministic tools and models are suitable to guarantee the safe operation of these systems. A necessity arises to develop and use methods that deal with uncertainties in the analysis. Several methodologies have been proposed to assess the transient stability of power systems considering uncertainties. However, most of these techniques are based on the execution of successive simulations, requiring a high computational effort. Hence, they are limited to off-line applications in small systems. In view of the foregoing, this work proposes the development of two methodologies to assess – in real time – the transient stability of power systems with parametric and operational uncertainties. The first one is an extension of PEBS, which is a direct method for stability assessment. This method, called robust PEBS, employs an interval energy function of the power system to determine a robust estimate critical clearing time. The second one is the use of optimization methods to find a robust estimate critical clearing time. Notably, we employ the Simulated Annealing and Differential Evolution algorithms. Besides developing methods to estimate the critical clearing time, this work also contributes to the analysis of power systems with uncertainties by introducing a technique to reduce the analysis effort. To be specific, a methodology is proposed to identify the most influential parameters for the transient analysis assessment based on a sensitivity analysis of the generator angles with respect to the system parameters.